Vietnam science and technology enterprises: Status and solutions for development - Anh, Nguyen Van; Ha, Nguyen Hong; Toan, Le Vu (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Development of science and technology (S&T) enterprises is one of the important tasks defined and implemented with full efforts by the Party and the State of Vietnam. Up to recent time, however, the development works face certain difficulties and troubles. The paper provides an overview of the development status of S&T enterprises in actual context and, then, proposes solutions to push up the establishment and development of this specific type of enterprises in Vietnam in the future. Code: 14082501